PENDIDIKAN KARAKTERMELALUI PENDEKATAN PENANAMAN NILAI DANPENDEKATAN PERKEMBANGAN MORAL KOGNITIF - Sadam Fajar Shodiq (AT-TAJDID, 2017)
Internalization approach is a value investment technique which has the target at the stage of ownership value that blends into the personality of the student, or to the extent of characterization. The stages of this internalization technique are (1) the stage of value transformation(2) the stage of the value transaction and (3) the stage of trans-internalization. This Cognitive Moral Development Approach is aimed to encourage students to think actively about moral issues and make moral decisions. According to this approach, moral development was seen as a development of level of thinking in making moral judgments, from a lower level to the higher level of thinking. This approach was done in several stages, those were through: (1) presenting moral dilemmas. (2) after the problematic moral dilemmas presented, followed by deviding group discussions. After that, (3) bring the results of group discussions to the class discussions, with the aim of clarifying values, creating alternatives and consequences; (4) after students discussing intensively and selecting some of selected values based on the alternative proposed, then they can organize the values selected into themselves.Keywords:Character, Education, Cognitive ,Moral, Development .